2016
DOI: 10.1104/pp.16.00780
|View full text |Cite
|
Sign up to set email alerts
|

NAD Acts as an Integral Regulator of Multiple Defense Layers

Abstract: (J.T.).Pyridine nucleotides, such as NAD, are crucial redox carriers and have emerged as important signaling molecules in stress responses. Previously, we have demonstrated in Arabidopsis (Arabidopsis thaliana) that the inducible NAD-overproducing nadC lines are more resistant to an avirulent strain of Pseudomonas syringae pv tomato (Pst-AvrRpm1), which was associated with salicylic acid-dependent defense. Here, we have further characterized the NAD-dependent immune response in Arabidopsis. Quinolinate-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 90 publications
(140 reference statements)
5
79
0
Order By: Relevance
“…This is accompanied by the accumulation of SA, JA and ABA as has been shown in NAD C -infiltrated leaves. 5 [Ca 2C ] cyt response was dose-dependent, could be mimicked by the positive controls ADPr/H 2 O 2 and was particularly intense upon NADP C application, thus suggesting its effect was explained by the donation of its ADPr moiety to form cyclic ADPr and NAADP so as to release Ca 2C from intracellular compartments. [1][2][3] In conclusion, our study revealed that pyridine nucleotides modulated Ca 2C fluxes in Arabidopsis.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…This is accompanied by the accumulation of SA, JA and ABA as has been shown in NAD C -infiltrated leaves. 5 [Ca 2C ] cyt response was dose-dependent, could be mimicked by the positive controls ADPr/H 2 O 2 and was particularly intense upon NADP C application, thus suggesting its effect was explained by the donation of its ADPr moiety to form cyclic ADPr and NAADP so as to release Ca 2C from intracellular compartments. [1][2][3] In conclusion, our study revealed that pyridine nucleotides modulated Ca 2C fluxes in Arabidopsis.…”
mentioning
confidence: 92%
“…4 Recently, we have detailed the NAD-inducible defense responses that are effective against biotrophic and necrotrophic pathogens. 5 Our study reveals that NAD C acts as an elicitor by stimulating basal defenses (i.e. ROS production, callose deposition, cell death) and influencing hormonal balance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…sugars, and other metabolites involved in central metabolism (Supplemental Methods S1; Paglia et al, 2012;Pétriacq et al, 2016). Accurately detected mass-to-charge features (error = 0.4 ppm) in negative (ESI 2 ; 17,326 ions) and positive (ESI + ; 18,341 ions) ionization modes were integrated using XCMS (Smith et al, 2006).…”
Section: Development Of Single and Double Mutants For The Ndufs8 Subumentioning
confidence: 99%